STRATEGY OF GILL NET FISHING OPERATIONS FOR COASTAL FISHERIES MANAGEMENT IN BATANG REGENCY - Rochmat, Rochmat; Mudzakir, Abdul Kohar; Santoso, Agus; Sudarmo, Agnes Puspitasari (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Batang Regency is located on the North Coast of Central Java, with geographical coordinates between 6°51'46" - 7°11'47" South Latitude and 109°40'19" - 110°03'06" East Longitude. This study aims to determine fisheries statistics, analyze business feasibility, and identify environmentally friendly fishing gear and strategies for managing fishing efforts. The method used in this research is purposive sampling. In addition, the method of interviewing social respondents was used. Methods of data analysis using business feasibility analysis, descriptive analysis with a quantitative approach, and SWOT. The results of this study included: an increase in the number of fishing gear indicating the intensity of fishing trips and the number of catches; gill net capture fisheries business with financial analysis obtained a PP value of 0.67 and an NPV value of Rp. 178,467,972, - the Net B/C value obtained was 5 and the IRR value obtained was 117%; environmentally friendly fishing gear based on the Code of Conduct for Responsible Fisheries (CCRF) gets a score of 30 and shows that gill net fishing gear is classified as environmentally friendly fishing gear; and there are gill net fishing gear management strategies such as increasing fishing activities, stabilizing the price of fish caught, developing port facilities, fostering the use of business management fishing technology and diversifying catches in the utilization of natural resource potential.